Upaya Menanggulangi Sampah Menjadi Sumber Daya Untuk Meningkatkan Kualitas dan Ekonomi Masyarakat - Galih, Aknes; Febrilia Rustina Arfiani (Universitas Duta Bangsa Surakarta, 2022)
Waste is unwanted or useless residual material after the end of a process. The waste problem is a common problem and has become a universal phenomenon in various countries in the world. The current waste problem that hit Central Java is that there are 33 Final Processing Sites (TPA) in Central Java that are unable to accommodate community waste shipments anymore. Based on the contents of the background above, it raises the question of how to manage household waste, so that the quality of the environment and the economy of the community increases and waste becomes a resource. This research method uses a normative juridical approach by examining theories, concepts, legal principles and legislation related to this research. Based on the research results, waste can be processed into a creative economy for the community, by utilizing eco-enzymes.